The relationship between service quality and customer satisfaction: a case study at Nh Beji Pharmacy - Budianto, Arif; Pradani, Dea Yulinestria; Rachmania, Nindita; Widiantoro, Edwin; Damanik, Alaris Darasito; Cahyono, Dwi (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2022)
Customer satisfaction is a critical indicator of the quality of pharmaceutical services and products pharmacies provide. It holds strategic importance in the pharmacy sector, significantly influencing repeat patronage and referrals. Satisfied customers are more likely to recommend the pharmacy to others, which can substantially contribute to the business's long-term growth. This study identifies service variables at Nh Beji Pharmacy that enhance customer satisfaction and evaluates their impact on patients' loyalty and their propensity to refer new customers. By exploring the link between customer satisfaction, repeat business, and referrals, the study aims to highlight the value of customer-focused services in pharmacies. Through interviews with 55 patients randomly selected from service records and provided informed consent for the 2019-2020 period, the study identified seven service variables that significantly boost customer satisfaction at Nh Beji Pharmacy. The findings demonstrate a notable correlation between customer satisfaction and patients' willingness to return and recommend the pharmacy, underscoring the importance of prioritizing customer satisfaction in pharmaceutical service delivery.